Modifikasi Alat Pemarut Kelapa Sistem Mekanis Dengan Mata Pisau Setengah Lingkaran - Marten E. Manane; Daud P. Mangesa; Defmit B.N. Riwu (Jurusan Teknik Mesin, Fakultas Sains dan Teknik, Universitas Nusa Cendana, 2021)
Today's increasingly rapid technology encourages people to continue to innovate in creating facilities and infrastructure to improve work efficiency and effectiveness. The aim of this research is to modify the mechanical system coconut grater with a semi-circular blade equipped with a coconut shell clamp. The manufacture of this coconut grater tool with a semi-circular blade uses the standard VDI 2221 design method. The design and technical drawings of the tool use the Autodesk Inventor software 2008 and the design is then realized according to the technical drawings. The result of this research is a coconut grater with a driving motor power of 0.2 kW. In this study, this coconut grater tool was used in grating coconut whether it worked according to the design drawing or not. The end result of making this tool is that it can be successfully made and can be used